High-strength aluminum-based bright tin wire and semi-automatic preparation method thereof
By using the combination of aluminum alloy matrix, Cu-Zn alloy base layer, Ni-Mo-P intermediate alloy layer and bright Sn-Sb alloy layer, the problems of low strength of aluminum-based tin plating wire and easy to fall off are solved, and high Strength, stability and high-speed plating effects.
Patent Information
- Application Number
- CN202411382033.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing aluminum-based tin-plating wire has low strength, the tin coating is prone to fall off, and the automatic plating speed is limited.
The preparation method of high-strength aluminum-based bright tin wire material is adopted, from the inside to the outside, the aluminum alloy matrix, the Cu-Zn alloy bottom layer, the Ni-Mo-P intermediate alloy layer and the bright Sn-Sb alloy layer, and the smelting and casting through an intermediate frequency furnace. , extrusion and electroplating process preparation to improve the density and hardness of the plating layer.
The strength of aluminum-based bright tin wire is significantly improved, the tensile strength is increased by more than 30%, the plating stability and burn resistance are good, and the plating speed is improved, avoiding the problem of overflow and short circuit of the plating foam.
Smart Images

Figure CN119265460A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength aluminum-based bright tin wire and a semi-automatic preparation method thereof, belonging to the technical field of aluminum-based materials and surface treatment thereof. Background Art
[0002] The crystal of aluminum alloy substrate is a face-centered cubic structure with good plasticity and toughness. Due to its good physical properties and low cost, it is widely used in various industries. The application scenarios of aluminum-based materials are determined by the matrix composition, workpiece shape, and surface treatment method. Aluminum-based wires with specific surface treatment are often used as electrode matrix materials in the energy storage battery industry and hydrometallurgical industry.
[0003] With lightweight metal aluminum as the inner core, aluminum-lead layered composite materials and Pb alloy energy-saving electrodes are prepared by anti-gravity method. Low melting point metal Bi, Sb or Sn is introduced to form a micro-alloyed lead alloy layer at the bonding interface between Al and Pb, obtaining a "sandwich" type lead-clad aluminum composite electrode material. The fluidity of the lead alloy liquid is poor and large-size electrode plates show local pitting corrosion. The coating has grain boundary gaps. The oxygen generated by electrolysis oxidizes the matrix through the grain boundary gaps of the coating, thereby deteriorating the electrode performance.
[0004] The fence-type anode plate used for non-ferrous metal electrowinning uses cheap aluminum rods as the substrate and a layer of lead alloy as the composite. The material cost is significantly reduced, but there are still problems with interface resistance and short life.
[0005] After ordinary aluminum-based tin-plated wire is produced, the tin layer is not firmly coated with lead alloy, which can easily block the outlet die hole, resulting in serious segregation of aluminum-lead composite rods. In addition, the existing aluminum-based tin-plated wire generally uses industrial pure aluminum as the base material, resulting in low strength. The surface tin coating of the wire has low hardness and slow plating speed, which leads to the tin layer falling off easily and the automated electroplating routing speed is limited. Summary of the invention
[0006] In view of the technical problems of low strength, easy detachment of tin coating and slow plating speed of current aluminum-based tin-plated wires, the present invention proposes a high-strength aluminum-based bright tin wire and a semi-automatic preparation method thereof. The high-strength aluminum-based bright tin wire of the present invention is composed of an aluminum alloy matrix, a Cu-Zn alloy bottom layer, a Ni-Mo-P intermediate alloy layer and a bright Sn-Sb alloy layer from the inside to the outside; the aluminum alloy matrix is formed by melting, casting, punch cutting and extrusion in a medium-frequency furnace, and then the aluminum alloy wire matrix is placed in an aluminum alloy wire electroplating production line for automatic surface metallization treatment, which includes aluminum alloy wire matrix pay-off, aluminum alloy wire matrix pretreatment, electroplating of Cu-Zn alloy bottom layer, chemical plating of Ni-Mo-P intermediate alloy layer, electroplating of bright Sn or Sn-Sb alloy layer, drying and winding, to prepare a high-strength aluminum-based bright tin wire. Compared with industrial pure aluminum, the high-strength aluminum-based bright tin wire of the present invention has a strength improvement of more than 30%.
[0007] A high-strength aluminum-based bright tin wire, which comprises, from the inside to the outside, an aluminum alloy matrix 1, a Cu-Zn alloy bottom layer 2, a Ni-Mo-P intermediate alloy layer 3 and a bright Sn or Sn-Sb alloy layer 4;
[0008] In terms of mass percentage of the aluminum alloy substrate 1, the aluminum alloy substrate 1 contains 0.4-0.8% Mg, 0.3-0.6% Si, 0.1-0.3% Mn, 0.01-0.1% Ca, 0.05-0.3% Zn, 0.0001-0.01% B, 0.001-0.1% Ti, Fe≤0.1%, and the balance is Al;
[0009] Calculated by mass percentage of the Cu-Zn alloy bottom layer 2, the Cu-Zn alloy bottom layer 2 contains 60-80% Cu and the remainder is Zn;
[0010] In terms of mass percentage of the Ni-Mo-P intermediate alloy layer 3, the Ni-Mo-P intermediate alloy layer 3 contains 0.1-0.5% Mo, 2.0-8.0% P, and the balance is Ni;
[0011] Calculated by mass percentage of the bright Sn-Sb alloy layer 4, the bright Sn-Sb alloy layer 4 contains 1-8% Sb, with the remainder being Sn.
[0012] Preferably, the diameter of the aluminum alloy substrate 1 is 2 to 8 mm, and the surface of the aluminum alloy substrate 1 is uniformly provided with arc-shaped grooves along the circumferential direction, the depth of the arc-shaped grooves is 0.01 to 0.1 mm, and the width of the arc-shaped grooves is 0.01 to 0.1 mm; the thickness of the Cu-Zn alloy bottom layer 2 is 0.1 to 1 μm; the thickness of the Ni-Mo-P intermediate alloy layer 3 is 0.5 to 3 μm; the thickness of the bright Sn or Sn-Sb alloy layer 4 is 1 to 8 μm.
[0013] The semi-automatic preparation method of the high-strength aluminum-based bright tin wire comprises the following specific steps:
[0014] S1. Preparing an aluminum alloy wire substrate, specifically comprising:
[0015] S11. Add pure aluminum ingots, aluminum-manganese alloy ingots, aluminum-silicon alloy ingots, aluminum-titanium-boron particles, pure zinc ingots, aluminum-calcium alloy ingots and aluminum-magnesium alloy ingots into a medium frequency melting furnace, heat to a temperature of 680-720°C to melt to form an aluminum alloy melt, keep the temperature for 1-2 hours, and then add the refining agent ZnCl 2 Refining, slagging, casting and cutting to form an aluminum alloy cylinder; preferably, the diameter of the aluminum alloy cylinder is 80 to 120 mm and the length is 300 to 400 mm;
[0016] S12. The aluminum alloy cylinder is preheated at a temperature of 180 to 240 ° C, extruded by an extruder to obtain an aluminum alloy wire, and the aluminum alloy wire is annealed at a temperature of 350 to 440 ° C for 1 to 3 hours to obtain an aluminum matrix rod; preferably, the diameter of the aluminum matrix rod is 8 to 12 mm;
[0017] S13. The aluminum matrix rod is plastically extruded through the groove of the extrusion wheel to obtain an aluminum alloy wire matrix; specifically, the aluminum matrix rod is placed in the groove of the extrusion wheel, and the extrusion wheel is driven by a motor (power 150-200kW) to rotate clockwise along the direction in which the aluminum matrix rod enters, and the aluminum matrix rod is dragged into the extrusion cavity formed by the extrusion wheel and the die cavity under the action of the friction between the compaction wheel and the groove wall, and 4 aluminum wires with the same diameter are plastically extruded through the die opening at a speed of 25-60m / min, and the wires are collected on a wire reel to obtain an aluminum alloy wire matrix;
[0018] S2. The aluminum alloy wire substrate is placed in an aluminum alloy wire electroplating production line for automated surface metallization treatment, which includes, in sequence, aluminum alloy wire substrate pay-off, aluminum alloy wire substrate pretreatment, electroplating of Cu-Zn alloy base layer, chemical plating of Ni-Mo-P intermediate alloy layer, electroplating of bright Sn or Sn-Sb alloy layer, drying and winding; specifically includes:
[0019] S21. The aluminum alloy wire substrate was degreased with NaOH solution, cleaned with deionized water, and then washed with HNO 3 Solution activation and deionized water washing to obtain a pretreated aluminum alloy wire substrate;
[0020] S22. The pretreated aluminum alloy wire substrate is placed in a Cu-Zn alloy plating solution for electroplating, and washed with deionized water to obtain a Cu-Zn alloy bottom layer;
[0021] S23. Plating the aluminum alloy wire substrate with the Cu-Zn alloy bottom layer in a chemical Ni-Mo-P alloy plating solution, and washing with deionized water to obtain a Ni-Mo-P intermediate alloy layer;
[0022] S24. Plating the aluminum alloy wire substrate with the chemically plated Ni-Mo-P intermediate alloy layer in a bright Sn or Sn-Sb alloy layer electroplating solution, and washing with deionized water to obtain a bright Sn or Sn-Sb alloy layer.
[0023] Preferably, the step S11. The aluminum-manganese alloy ingot is Al-5% Mn, the aluminum-silicon alloy ingot is Al-10% Si, the aluminum-titanium-boron particles are Al-3% Ti-0.5% B, the aluminum-calcium alloy ingot is Al-5% Ca and the aluminum-magnesium alloy ingot is A1-5% Mg; the refining agent ZnCl 2 The addition amount is 1 to 3% of the mass of the aluminum alloy melt.
[0024] Preferably, in step S2, the aluminum alloy wire substrate pay-off rate is 5 to 10 m / min.
[0025] Preferably, in step S21, the concentration of NaOH solution is 50-100 g / L, the degreasing temperature is 60-70°C, and the degreasing time is 40-60 s; HNO 3 The solution concentration is 20-50wt.%, the activation temperature is 20-40°C, and the activation time is 40-60s.
[0026] Preferably, the Cu-Zn alloy plating solution in step S22 contains 10-60 g / L copper sulfate, 8-20 g / L zinc oxide, 120-200 g / L potassium pyrophosphate, 10-20 g / L ethylenediaminetetraacetic acid, and 1-2 ml / L OP emulsifier; the electroplating temperature is 20-40°C, and the cathode current density is 0.5-2 A / dm 2 , the electroplating time is 0.5 to 2 minutes.
[0027] Preferably, the step S23. The chemical plating Ni-Mo-P alloy solution contains 15-45 g / L nickel sulfate, 5-20 g / L sodium hypophosphite, 5-10 g / L potassium molybdate, and 0.01-0.5 g / L polyethylene glycol 6000, and the pH value of the chemical plating Ni-Mo-P alloy solution is 4.0-5.0; the temperature of the chemical plating is 90-100°C, and the time is 5-10 min.
[0028] Preferably, the S24. bright Sn layer electroplating solution contains 40-50 g / L Sn 2+ , 100-160g / L methanesulfonic acid, 5-30g / L high-speed tin plating additive; the bright Sn-Sb alloy layer electroplating solution contains 40-50g / L Sn 2+ , 1~5g / LSb 3+ , 100-160g / L methanesulfonic acid, 5-30g / L high-speed tin plating additive; electroplating temperature is 20-50℃, cathode current density is 5-40A / dm 2, the electroplating time is 20 to 300s.
[0029] Preferably, the high-speed tin plating additive contains 4-6wt.% methanesulfonic acid, 10-20wt.% surfactant, 1-8wt.% brightener, 0.1-0.5wt.% leveler, 0.1-0.5wt.% stabilizer, 0.1-0.5wt.% anti-scorch agent, and the balance is deionized water.
[0030] More preferably, the surfactant is a polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900 or 3800, C 12 -C 14 The invention discloses a method for preparing the coating of the present invention comprising: preparing the coating of the present invention comprises: preparing the coating of the present invention comprises one or more combinations of alcohol polyoxyethylene ether sodium sulfate and tristyrylphenol polyoxyethylene ether ammonium sulfate; the brightener is one or more combinations of glutaraldehyde, benzyl acetone and acrylic acid; the leveling agent is pyridine-2-carboxylic acid; the stabilizer is a combination of ascorbic acid and hydroquinone; and the anti-scorching agent is sodium lauroyl glutamate.
[0031] The beneficial effects of the present invention are:
[0032] (1) The present invention adds a specific content of boron to the aluminum alloy to reduce the resistivity, adds a specific content of titanium to refine the metal grain structure, adds specific contents of Mn and Si to improve the corrosion resistance and strength, and adds specific contents of Ca and Mg to form a solid solution with aluminum to improve the strength of the aluminum alloy. Compared with industrial pure aluminum, the strength is increased by more than 30%;
[0033] (2) Due to the high pressure and temperature generated by friction, the aluminum alloy undergoes thermoplastic deformation in the mold cavity. The present invention uses the extrusion wheel groove plastic extrusion method to prepare aluminum alloy wire substrates with different surfaces;
[0034] (3) The present invention adopts chemical plating to prepare the Ni-Mo-P intermediate layer, which can improve the compactness and hardness of the Ni-Mo-P coating. At the same time, a small amount of Sb in the Sn-Sb alloy layer can improve the compactness and hardness of the coating, which is beneficial to the subsequent extrusion coating of the wire with lead alloy and will not cause the coating to fall off.
[0035] (4) The present invention adopts polyoxyethylene-polyoxypropylene block polymer as the main surface dispersant of the high-speed tin plating additive, and when the current density can vary in a large area, a good and qualified uniform coating can still be obtained, thereby achieving high-speed tin plating and optimizing the stability of the plating solution. In particular, an amino acid amphoteric surfactant is introduced as an anti-scorching agent to increase the anti-scorching property of the cathode at high current density;
[0036] (5) The plating solution for electroplating a bright Sn-Sb alloy layer of the present invention has excellent defoaming ability, which can avoid short circuits and difficulties in production site management caused by foam overflow during high-flow rate circulation of the plating solution. At the same time, the consumption of additives during electroplating is small, and the plating solution has high stability. After an accelerated simulation test of 1000A·h / L, the performance is still stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The schematic diagram of the structure of high-strength aluminum-based bright tin wire; in the figure, 1-aluminum alloy matrix, 2-Cu-Zn alloy bottom layer, 3-Ni-Mo-P intermediate alloy layer, 4-bright Sn or Sn-Sb alloy layer.
[0038] Figure 2 It is a comparison diagram of the tensile stress-strain curve of Example 1 and industrial pure aluminum wire with the same external dimensions.
[0039] Figure 3 It is a comparison diagram of the tensile stress-strain curve of Example 2 and industrial pure aluminum wire with the same external dimensions.
[0040] Figure 4 It is a comparison diagram of the tensile stress-strain curve of Example 3 and the industrial pure aluminum wire with the same external dimensions.
[0041] Figure 5 It is a comparison diagram of the tensile stress-strain curve of Example 4 and the industrial pure aluminum wire with the same external dimensions. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0043] Example 1: A high-strength aluminum-based bright tin wire (see Figure 1 ), from the inside to the outside, it is an aluminum alloy substrate 1, a Cu-Zn alloy bottom layer 2, a Ni-Mo-P intermediate alloy layer 3 and a bright Sn-Sb alloy layer 4;
[0044] In terms of mass percentage of the aluminum alloy substrate 1, the aluminum alloy substrate 1 contains 0.6% Mg, 0.4% Si, 0.1% Mn, 0.06% Ca, 0.1% Zn, 0.005% B, 0.05% Ti, 0.05% Fe, and the balance is Al;
[0045] Calculated by mass percentage of the Cu-Zn alloy bottom layer 2, the Cu-Zn alloy bottom layer 2 contains 70% Cu and the remainder is Zn;
[0046] Calculated by mass percentage of the Ni-Mo-P intermediate alloy layer 3, the Ni-Mo-P intermediate alloy layer 3 contains 0.3% Mo, 5% P, and the balance is Ni;
[0047] In terms of mass percentage of the bright Sn-Sb alloy layer 4, the bright Sn-Sb alloy layer 4 contains 4% Sb, and the balance is Sn;
[0048] The diameter of the aluminum alloy substrate 1 is 2 mm, and the surface of the aluminum alloy substrate 1 is uniformly provided with arc-shaped grooves along the circumferential direction, the depth of the arc-shaped grooves is 0.05 mm, and the width of the arc-shaped grooves is 0.05 mm; the thickness of the Cu-Zn alloy bottom layer 2 is 0.5 μm; the thickness of the Ni-Mo-P intermediate alloy layer 3 is 2 μm; the thickness of the bright Sn-Sb alloy layer 4 is 4 μm;
[0049] The semi-automatic preparation method of the high-strength aluminum-based bright tin wire comprises the following specific steps:
[0050] S1. Preparing an aluminum alloy wire substrate, specifically comprising:
[0051] S11. Add pure aluminum ingots, aluminum-manganese alloy ingots (Al-5% Mn), aluminum-silicon alloy ingots (Al-10% Si), aluminum-titanium-boron particles (Al-3% Ti-0.5% B), pure zinc ingots, aluminum-calcium alloy ingots (Al-5% Ca) and aluminum-magnesium alloy ingots (Al-5% Mg) into a medium frequency melting furnace, heat to 700°C to melt to form an aluminum alloy melt, keep the temperature for 1 hour, and then add the refining agent ZnCl 2 Refining, slagging, casting and cutting are performed to form an aluminum alloy cylinder; the diameter of the aluminum alloy cylinder is 80 mm and the length is 400 mm; the refining agent ZnCl 2 The addition amount is 2% of the mass of the aluminum alloy melt;
[0052] S12. The aluminum alloy cylinder is preheated at a temperature of 200° C., extruded by an extruder to obtain an aluminum alloy wire, and the aluminum alloy wire is annealed at a temperature of 400° C. for 2 h to obtain an aluminum matrix rod (with a diameter of 8 mm);
[0053] S13. The aluminum matrix rod is plastically extruded through the groove of the extrusion wheel to obtain an aluminum alloy wire matrix; specifically, the aluminum matrix rod is placed in the groove of the extrusion wheel, and the extrusion wheel is driven by a motor (power 180kW) to rotate clockwise along the direction in which the aluminum matrix rod enters, and the aluminum matrix rod is dragged into the extrusion cavity formed by the extrusion wheel and the die cavity under the action of the friction between the compaction wheel and the groove wall, and 4 aluminum wires of the same diameter are plastically extruded through the die opening at a speed of 25m / min, and the wires are collected on a wire reel to obtain an aluminum alloy wire matrix;
[0054] S2. The aluminum alloy wire substrate is placed in an aluminum alloy wire electroplating production line for automated surface metallization treatment, which includes, in sequence, aluminum alloy wire substrate pay-off (pay-off rate is 10 m / min), aluminum alloy wire substrate pretreatment, electroplating Cu-Zn alloy base layer, chemical plating Ni-Mo-P intermediate alloy layer, electroplating bright Sn-Sb alloy layer, drying and winding; specifically includes:
[0055] S21. The aluminum alloy wire substrate was degreased with a 100 g / L NaOH solution (degreased at 60 °C for 40 s), washed with deionized water, and washed with 40 wt.% HNO 3 Solution activation (activation at 30°C for 30s) and deionized water washing to obtain a pretreated aluminum alloy wire substrate;
[0056] S22. The pretreated aluminum alloy wire substrate is placed in a Cu-Zn alloy plating solution for electroplating (electroplating temperature is 30°C, cathode current density is 1.5A / dm 2 , electroplating time is 1min), and after washing with deionized water, a Cu-Zn alloy bottom layer is obtained; the Cu-Zn alloy plating solution contains 50g / L copper sulfate, 15g / L zinc oxide, 160g / L potassium pyrophosphate, 15g / L ethylenediaminetetraacetic acid, and 1ml / LOP emulsifier;
[0057] S23. Plating the aluminum alloy wire substrate with the Cu-Zn alloy bottom layer in a chemically plated Ni-Mo-P alloy solution for chemical plating (the temperature of the chemical plating is 95° C. and the time is 10 min), and washing with deionized water to obtain a Ni-Mo-P intermediate alloy layer; the chemically plated Ni-Mo-P alloy solution contains 30 g / L nickel sulfate, 10 g / L sodium hypophosphite, 5 g / L potassium molybdate, and 0.3 g / L polyethylene glycol 6000, and the pH value of the chemically plated Ni-Mo-P alloy solution is 4.6;
[0058] S24. The aluminum alloy wire substrate with chemically plated Ni-Mo-P intermediate alloy layer is placed in a bright Sn-Sb alloy layer electroplating solution (electroplating temperature is 30°C, cathode current density is 20A / dm 2 , electroplating time is 0.5min), and a bright Sn-Sb alloy layer is obtained after washing with deionized water; the bright Sn-Sb alloy layer electroplating solution contains 50g / L Sn 2+ , 5g / LSb 3+ , 120g / L methanesulfonic acid, 20g / L high-speed tin plating additive; based on the mass of the high-speed tin plating additive as 100%, the high-speed tin plating additive contains 5wt.% methanesulfonic acid, 15wt.% surfactant (polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900, C 12 -C 14A composition of alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether ammonium sulfate, a polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900, C 12 -C 14 Alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether sulfate ammonium salt in a mass ratio of 5:1:1), 4wt.% brightener (a composition of glutaraldehyde, benzyl acetone, and acrylic acid, the mass ratio of glutaraldehyde, benzyl acetone, and acrylic acid is 10:2:1), 0.5wt.% leveler (pyridine-2-carboxylic acid), 0.5wt.% stabilizer (a composition of ascorbic acid and hydroquinone, the mass ratio of ascorbic acid and hydroquinone is 1:1), 0.5wt.% anti-scorching agent (sodium lauroyl glutamate), and the balance is deionized water;
[0059] The tensile strength of the high-strength aluminum-based bright tin wire of this embodiment is 128-130 MPa, which is about 30.6% higher than that of the 1070 pure aluminum wire (tensile strength is 98-100 MPa) of the same size;
[0060] The high-speed tin plating technology used in this embodiment has high stability, good anti-scorching performance, and good defoaming ability compared to traditional ordinary tin plating technology. The electrodeposition speed can reach 8μm / min~10μm / min, and the cathode current density is 20A / dm 2 Compared with the traditional bright tin plating deposition rate (about 3μm / min~4μm / min), it is more than 2 times higher, and compared with the traditional bright tin plating cathode current density (3 / dm 2 ~5A / dm 2 ) increased by about 5 times.
[0061] Example 2: A high-strength aluminum-based bright tin wire (see Figure 1 ), from the inside to the outside, it is an aluminum alloy substrate 1, a Cu-Zn alloy bottom layer 2, a Ni-Mo-P intermediate alloy layer 3 and a bright Sn-Sb alloy layer 4;
[0062] In terms of mass percentage of the aluminum alloy substrate 1, the aluminum alloy substrate 1 contains 0.4% Mg, 0.3% Si, 0.1% Mn, 0.01% Ca, 0.05% Zn, 0.01% B, 0.01% Ti, 0.01% Fe, and the balance is Al;
[0063] Calculated by mass percentage of the Cu-Zn alloy bottom layer 2, the Cu-Zn alloy bottom layer 2 contains 60% Cu and the remainder is Zn;
[0064] In terms of mass percentage of the Ni-Mo-P intermediate alloy layer 3, the Ni-Mo-P intermediate alloy layer 3 contains 0.1% Mo, 20% P, and the balance is Ni;
[0065] In terms of mass percentage of the bright Sn-Sb alloy layer 4, the bright Sn-Sb alloy layer 4 contains 1% Sb, and the balance is Sn;
[0066] The diameter of the aluminum alloy substrate 1 is 2 mm, and the surface of the aluminum alloy substrate 1 is uniformly provided with arc-shaped grooves along the circumferential direction, the depth of the arc-shaped grooves is 0.01 mm, and the width of the arc-shaped grooves is 0.01 mm; the thickness of the Cu-Zn alloy bottom layer 2 is 0.1 μm; the thickness of the Ni-Mo-P intermediate alloy layer 3 is 0.5 μm; the thickness of the bright Sn-Sb alloy layer 4 is 2 μm;
[0067] The semi-automatic preparation method of the high-strength aluminum-based bright tin wire comprises the following specific steps:
[0068] S1. Preparing an aluminum alloy wire substrate, specifically comprising:
[0069] S11. Add pure aluminum ingots, aluminum-manganese alloy ingots (Al-5% Mn), aluminum-silicon alloy ingots (Al-10% Si), aluminum-titanium-boron particles (Al-3% Ti-0.5% B), pure zinc ingots, aluminum-calcium alloy ingots (Al-5% Ca) and aluminum-magnesium alloy ingots (Al-5% Mg) into a medium frequency melting furnace, heat to 680°C to melt to form an aluminum alloy melt, keep the temperature for 1 hour, and then add the refining agent ZnCl 2 Refining, slagging, casting and cutting are performed to form an aluminum alloy cylinder; preferably, the diameter of the aluminum alloy cylinder is 80 mm and the length is 400 mm; the refining agent ZnCl 2 The addition amount is 1% of the mass of the aluminum alloy melt;
[0070] S12. The aluminum alloy cylinder was preheated at 180°C, extruded by an extruder to obtain an aluminum alloy wire, and the aluminum alloy wire was annealed at 350°C for 1h to obtain an aluminum matrix rod (with a diameter of 8 mm);
[0071] S13. The aluminum matrix rod is plastically extruded through the groove of the extrusion wheel to obtain an aluminum alloy wire matrix; specifically, the aluminum matrix rod is placed in the groove of the extrusion wheel, and the extrusion wheel is driven by a motor (power 180kW) to rotate clockwise along the direction in which the aluminum matrix rod enters, and the aluminum matrix rod is dragged into the extrusion cavity formed by the extrusion wheel and the die cavity under the action of the friction between the compaction wheel and the groove wall, and 4 aluminum wires of the same diameter are plastically extruded through the die opening at a speed of 25m / min, and the wires are collected on a wire reel to obtain an aluminum alloy wire matrix;
[0072] S2. The aluminum alloy wire substrate is placed in an aluminum alloy wire electroplating production line for automated surface metallization treatment, which includes, in sequence, aluminum alloy wire substrate pay-off (pay-off rate is 5 m / min), aluminum alloy wire substrate pretreatment, electroplating Cu-Zn alloy base layer, chemical plating Ni-Mo-P intermediate alloy layer, electroplating bright Sn-Sb alloy layer, drying and winding; specifically includes:
[0073] S21. The aluminum alloy wire substrate was degreased with a 50 g / L NaOH solution (degreased at 60 °C for 40 s), washed with deionized water, and washed with 20 wt.% HNO 3 Solution activation (activation at 20°C for 40s) and deionized water washing to obtain a pretreated aluminum alloy wire substrate;
[0074] S22. The pretreated aluminum alloy wire substrate is placed in a Cu-Zn alloy plating solution for electroplating (electroplating temperature is 20°C, cathode current density is 0.5A / dm 2 , electroplating time is 0.5min), and after washing with deionized water, a Cu-Zn alloy bottom layer is obtained; the Cu-Zn alloy plating solution contains 10g / L copper sulfate, 8g / L zinc oxide, 120g / L potassium pyrophosphate, 10g / L ethylenediaminetetraacetic acid, and 1ml / LOP emulsifier;
[0075] S23. Plating the aluminum alloy wire substrate with the Cu-Zn alloy bottom layer in a chemical Ni-Mo-P alloy plating solution for chemical plating (the chemical plating temperature is 95° C. and the time is 10 min), and washing with deionized water to obtain a Ni-Mo-P intermediate alloy layer; the chemical Ni-Mo-P alloy plating solution contains 15 g / L nickel sulfate, 5 g / L sodium hypophosphite, 5 g / L potassium molybdate, and 0.01 g / L polyethylene glycol 6000, and the pH value of the chemical Ni-Mo-P alloy plating solution is 4;
[0076] S24. The aluminum alloy wire substrate with chemically plated Ni-Mo-P intermediate alloy layer is placed in a bright Sn-Sb alloy layer electroplating solution (electroplating temperature is 30°C, cathode current density is 5A / dm 2 , electroplating time is 20s), and a bright Sn-Sb alloy layer is obtained after washing with deionized water; the bright Sn-Sb alloy layer electroplating solution contains 40g / L Sn 2+ , 1g / LSb 3+ , 100g / L methyl sulfonic acid, 5g / L high-speed tin plating additive; based on the mass of the high-speed tin plating additive as 100%, the high-speed tin plating additive contains 5wt.% methyl sulfonic acid, 15wt.% surfactant (polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 3800, C 12 -C 14A composition of alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether sulfate ammonium salt, a polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 3800, C 12 -C 14 Alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether sulfate ammonium salt in a mass ratio of 5:1:1), 4wt.% brightener (a composition of glutaraldehyde and benzyl acetone, the mass ratio of glutaraldehyde and benzyl acetone is 5:1), 0.5wt.% leveler (pyridine-2-carboxylic acid), 0.5wt.% stabilizer (a composition of ascorbic acid and hydroquinone, the mass ratio of ascorbic acid and hydroquinone is 1:1), 0.5wt.% anti-scorching agent (sodium lauroyl glutamate), and the balance is deionized water;
[0077] The tensile strength of the high-strength aluminum-based bright tin wire of this embodiment is 131-132 MPa, which is about 31.2% higher than that of the 1070 pure aluminum wire (tensile strength is 98-100 MPa) of the same size;
[0078] The high-speed tin plating technology used in this embodiment has high stability, good anti-scorching performance, and good defoaming ability compared to traditional ordinary tin plating technology. The electrodeposition speed can reach 6μm / min~8μm / min, which is about 100% higher than the traditional bright tin plating deposition rate (about 3μm / min~4μm / min).
[0079] Example 3: A high-strength aluminum-based bright tin wire (see Figure 1 ), from the inside to the outside, it is an aluminum alloy substrate 1, a Cu-Zn alloy bottom layer 2, a Ni-Mo-P intermediate alloy layer 3 and a bright Sn-Sb alloy layer 4;
[0080] In terms of mass percentage of the aluminum alloy substrate 1, the aluminum alloy substrate 1 contains 0.8% Mg, 0.6% Si, 0.3% Mn, 0.1% Ca, 0.3% Zn, 0.01% B, 0.1% Ti, 0.1% Fe, and the balance is Al;
[0081] Calculated by mass percentage of the Cu-Zn alloy bottom layer 2, the Cu-Zn alloy bottom layer 2 contains 80% Cu and the remainder is Zn;
[0082] In terms of mass percentage of the Ni-Mo-P intermediate alloy layer 3, the Ni-Mo-P intermediate alloy layer 3 contains 0.5% Mo, 8% P, and the balance is Ni;
[0083] In terms of mass percentage of the bright Sn-Sb alloy layer 4, the bright Sn-Sb alloy layer 4 contains 8% Sb, and the balance is Sn;
[0084] The diameter of the aluminum alloy substrate 1 is 6 mm, and the surface of the aluminum alloy substrate 1 is uniformly provided with arc-shaped grooves along the circumferential direction, the depth of the arc-shaped grooves is 0.08 mm, and the width of the arc-shaped grooves is 0.08 mm; the thickness of the Cu-Zn alloy bottom layer 2 is 1 μm; the thickness of the Ni-Mo-P intermediate alloy layer 3 is 3 μm; the thickness of the bright Sn-Sb alloy layer 4 is 8 μm;
[0085] The semi-automatic preparation method of the high-strength aluminum-based bright tin wire comprises the following specific steps:
[0086] S1. Preparing an aluminum alloy wire substrate, specifically comprising:
[0087] S11. Add pure aluminum ingots, aluminum-manganese alloy ingots (Al-5% Mn), aluminum-silicon alloy ingots (Al-10% Si), aluminum-titanium-boron particles (Al-3% Ti-0.5% B), pure zinc ingots, aluminum-calcium alloy ingots (Al-5% Ca) and aluminum-magnesium alloy ingots (Al-5% Mg) into a medium frequency melting furnace, heat to 720°C to melt to form an aluminum alloy melt, keep the temperature for 2 hours, and then add the refining agent ZnCl 2 Refining, slagging, casting and cutting are performed to form an aluminum alloy cylinder; preferably, the diameter of the aluminum alloy cylinder is 80 mm and the length is 400 mm; the refining agent ZnCl 2 The addition amount is 3% of the mass of the aluminum alloy melt;
[0088] S12. The aluminum alloy cylinder was preheated at a temperature of 240°C, extruded by an extruder to obtain an aluminum alloy wire, and the aluminum alloy wire was annealed at a temperature of 440°C for 3h to obtain an aluminum matrix rod (with a diameter of 12 mm);
[0089] S13. The aluminum matrix rod is plastically extruded through the groove of the extrusion wheel to obtain an aluminum alloy wire matrix; specifically, the aluminum matrix rod is placed in the groove of the extrusion wheel, and the extrusion wheel is driven by a motor (power 200kW) to rotate clockwise along the direction in which the aluminum matrix rod enters, and the aluminum matrix rod is dragged into the extrusion cavity formed by the extrusion wheel and the die cavity under the action of the friction between the compaction wheel and the groove wall, and 4 aluminum wires with the same diameter are plastically extruded through the die opening at a speed of 60m / min, and the wires are collected on a wire reel to obtain an aluminum alloy wire matrix;
[0090] S2. The aluminum alloy wire substrate is placed in an aluminum alloy wire electroplating production line for automated surface metallization treatment, which includes, in sequence, aluminum alloy wire substrate pay-off (pay-off rate is 15 m / min), aluminum alloy wire substrate pretreatment, electroplating Cu-Zn alloy base layer, chemical plating Ni-Mo-P intermediate alloy layer, electroplating bright Sn-Sb alloy layer, drying and winding; specifically includes:
[0091] S21. The aluminum alloy wire substrate was degreased with a 100 g / L NaOH solution (degreased at 70 °C for 60 s), washed with deionized water, and washed with 50 wt.% HNO 3 Solution activation (activation at 40°C for 60s) and deionized water washing to obtain a pretreated aluminum alloy wire substrate;
[0092] S22. The pretreated aluminum alloy wire substrate is placed in a Cu-Zn alloy plating solution for electroplating (electroplating temperature is 40°C, cathode current density is 2A / dm 2 , electroplating time is 2min), and after washing with deionized water, a Cu-Zn alloy bottom layer is obtained; the Cu-Zn alloy plating solution contains 60g / L copper sulfate, 20g / L zinc oxide, 200g / L potassium pyrophosphate, 20g / L ethylenediaminetetraacetic acid, and 2ml / L OP emulsifier;
[0093] S23. Plating the aluminum alloy wire substrate with the Cu-Zn alloy bottom layer in a chemically plated Ni-Mo-P alloy solution for chemical plating (the temperature of the chemical plating is 100° C. and the time is 10 min), and washing with deionized water to obtain a Ni-Mo-P intermediate alloy layer; the chemically plated Ni-Mo-P alloy solution contains 45 g / L nickel sulfate, 20 g / L sodium hypophosphite, 10 g / L potassium molybdate, and 0.5 g / L polyethylene glycol 6000, and the pH value of the chemically plated Ni-Mo-P alloy solution is 5.0;
[0094] S24. The aluminum alloy wire substrate with chemically plated Ni-Mo-P intermediate alloy layer is placed in a bright Sn-Sb alloy layer electroplating solution (electroplating temperature is 40°C, cathode current density is 40A / dm 2 , electroplating time is 0.5min), and a bright Sn-Sb alloy layer is obtained after washing with deionized water; the bright Sn-Sb alloy layer electroplating solution contains 50g / L Sn 2+ , 5g / LSb 3+ , 150g / L methanesulfonic acid, 20g / L high-speed tin plating additive; based on the mass of the high-speed tin plating additive as 100%, the high-speed tin plating additive contains 5wt.% methanesulfonic acid, 15wt.% surfactant (polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900, C 12 -C 14 A composition of alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether ammonium sulfate, a polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900, C 12 -C 14Alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether sulfate ammonium salt in a mass ratio of 5:1:1), 4wt.% brightener (a composition of glutaraldehyde, benzyl acetone, and acrylic acid, the mass ratio of glutaraldehyde, benzyl acetone, and acrylic acid is 10:2:1), 0.5wt.% leveler (pyridine-2-carboxylic acid), 0.5wt.% stabilizer (a composition of ascorbic acid and hydroquinone, the mass ratio of ascorbic acid and hydroquinone is 1:1), 0.5wt.% anti-scorching agent (sodium lauroyl glutamate), and the balance is deionized water;
[0095] The tensile strength of the high-strength aluminum-based bright tin wire in this embodiment is 87-89 MPa, which is about 35.9% higher than that of the 1070 pure aluminum wire with the same size (tensile strength is 64-5 MPa);
[0096] The high-speed tin plating technology used in this embodiment has high stability, good anti-scorching performance, and good defoaming ability compared to traditional ordinary tin plating technology. The electrodeposition speed can reach 16μm / min~20μm / min, and the cathode current density is 40A / dm 2 Compared with the traditional bright tin plating deposition rate (about 3μm / min~4μm / min), it is more than 4 times higher, and compared with the traditional bright tin plating cathode current density (3 / dm 2 ~5A / dm 2 ) increased by more than 7 times.
[0097] Example 4: A high-strength aluminum-based bright tin wire (see Figure 1 ), from the inside to the outside, it is an aluminum alloy substrate 1, a Cu-Zn alloy bottom layer 2, a Ni-Mo-P intermediate alloy layer 3 and a bright Sn layer 4;
[0098] In terms of mass percentage of the aluminum alloy substrate 1, the aluminum alloy substrate 1 contains 0.6% Mg, 0.4% Si, 0.1% Mn, 0.06% Ca, 0.1% Zn, 0.05% B, 0.05% Ti, 0.05% Fe, and the balance is Al;
[0099] Calculated by mass percentage of the Cu-Zn alloy bottom layer 2, the Cu-Zn alloy bottom layer 2 contains 70% Cu and the remainder is Zn;
[0100] Calculated by mass percentage of the Ni-Mo-P intermediate alloy layer 3, the Ni-Mo-P intermediate alloy layer 3 contains 0.3% Mo, 5% P, and the balance is Ni;
[0101] The diameter of the aluminum alloy substrate 1 is 8 mm, and the surface of the aluminum alloy substrate 1 is uniformly provided with arc-shaped grooves along the circumferential direction, the depth of the arc-shaped grooves is 0.1 mm, and the width of the arc-shaped grooves is 0.1 mm; the thickness of the Cu-Zn alloy bottom layer 2 is 0.5 μm; the thickness of the Ni-Mo-P intermediate alloy layer 3 is 2 μm; and the thickness of the bright Sn layer 4 is 4 μm;
[0102] The semi-automatic preparation method of the high-strength aluminum-based bright tin wire comprises the following specific steps:
[0103] S1. Preparing an aluminum alloy wire substrate, specifically comprising:
[0104] S11. Add pure aluminum ingots, aluminum-manganese alloy ingots (Al-5% Mn), aluminum-silicon alloy ingots (Al-10% Si), aluminum-titanium-boron particles (Al-3% Ti-0.5% B), pure zinc ingots, aluminum-calcium alloy ingots (Al-5% Ca) and aluminum-magnesium alloy ingots (Al-5% Mg) into a medium frequency melting furnace, heat to 70°C to melt to form an aluminum alloy melt, keep the temperature for 1 hour, and then add the refining agent ZnCl 2 Refining, slagging, casting and cutting are performed to form an aluminum alloy cylinder; preferably, the diameter of the aluminum alloy cylinder is 80 mm and the length is 400 mm; the refining agent ZnCl 2 The addition amount is 2% of the mass of the aluminum alloy melt;
[0105] S12. The aluminum alloy cylinder is preheated at a temperature of 200° C., extruded by an extruder to obtain an aluminum alloy wire, and the aluminum alloy wire is annealed at a temperature of 400° C. for 2 h to obtain an aluminum matrix rod (with a diameter of 8 mm);
[0106] S13. The aluminum matrix rod is plastically extruded through the groove of the extrusion wheel to obtain an aluminum alloy wire matrix; specifically, the aluminum matrix rod is placed in the groove of the extrusion wheel, and the extrusion wheel is driven by a motor (power 180kW) to rotate clockwise along the direction in which the aluminum matrix rod enters, and the aluminum matrix rod is dragged into the extrusion cavity formed by the extrusion wheel and the die cavity under the action of the friction between the compaction wheel and the groove wall, and 4 aluminum wires with the same diameter are plastically extruded through the die opening at a speed of 40m / min, and the wires are collected on a wire reel to obtain an aluminum alloy wire matrix;
[0107] S2. The aluminum alloy wire substrate is placed in an aluminum alloy wire electroplating production line for automated surface metallization treatment, which includes, in sequence, aluminum alloy wire substrate pay-off (pay-off rate is 10 m / min), aluminum alloy wire substrate pretreatment, electroplating Cu-Zn alloy base layer, chemical plating Ni-Mo-P intermediate alloy layer, electroplating bright Sn layer, drying and winding; specifically includes:
[0108] S21. The aluminum alloy wire substrate was degreased with a 100 g / L NaOH solution (degreased at 60 °C for 40 s), washed with deionized water, and washed with 40 wt.% HNO 3 Solution activation (activation at 30°C for 30s) and deionized water washing to obtain a pretreated aluminum alloy wire substrate;
[0109] S22. The pretreated aluminum alloy wire substrate is placed in a Cu-Zn alloy plating solution for electroplating (electroplating temperature is 30°C, cathode current density is 1.5A / dm 2 , electroplating time is 1min), and after washing with deionized water, a Cu-Zn alloy bottom layer is obtained; the Cu-Zn alloy plating solution contains 50g / L copper sulfate, 15g / L zinc oxide, 160g / L potassium pyrophosphate, 15g / L ethylenediaminetetraacetic acid, and 1ml / LOP emulsifier;
[0110] S23. Plating the aluminum alloy wire substrate with the Cu-Zn alloy bottom layer in a chemically plated Ni-Mo-P alloy solution for chemical plating (the temperature of the chemical plating is 95° C. and the time is 10 min), and washing with deionized water to obtain a Ni-Mo-P intermediate alloy layer; the chemically plated Ni-Mo-P alloy solution contains 30 g / L nickel sulfate, 10 g / L sodium hypophosphite, 5 g / L potassium molybdate, and 0.3 g / L polyethylene glycol 6000, and the pH value of the chemically plated Ni-Mo-P alloy solution is 4.6;
[0111] S24. The aluminum alloy wire substrate with chemically plated Ni-Mo-P intermediate alloy layer is placed in a bright Sn layer electroplating solution (electroplating temperature is 30°C, cathode current density is 25A / dm 2 , electroplating time is 0.5min), and a bright Sn layer is obtained after washing with deionized water; the bright Sn layer electroplating solution contains 50g / L Sn 2+ , 120g / L methanesulfonic acid, 20g / L high-speed tin plating additive; based on the mass of the high-speed tin plating additive as 100%, the high-speed tin plating additive contains 5wt.% methanesulfonic acid, 15wt.% surfactant (polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900, C 12 -C 14 A composition of alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether ammonium sulfate, a polyoxyethylene-polyoxypropylene block polymer with an average molecular weight of 2900, C 12 -C 14Alcohol polyoxyethylene ether sodium sulfate, tristyrylphenol polyoxyethylene ether sulfate ammonium salt in a mass ratio of 5:1:1), 4wt.% brightener (a composition of glutaraldehyde, benzyl acetone, and acrylic acid, the mass ratio of glutaraldehyde, benzyl acetone, and acrylic acid is 10:2:1), 0.5wt.% leveler (pyridine-2-carboxylic acid), 0.5wt.% stabilizer (a composition of ascorbic acid and hydroquinone, the mass ratio of ascorbic acid and hydroquinone is 1:1), 0.5wt.% anti-scorching agent (sodium lauroyl glutamate), and the balance is deionized water;
[0112] The tensile strength of the high-strength aluminum-based bright tin wire in this embodiment is 72-74 MPa, which is about 24.1% higher than that of the 1070 pure aluminum wire with the same outer dimensions (tensile strength is 58-60 MPa);
[0113] The high-speed tin plating technology used in this embodiment has high stability, good anti-scorching performance, and good defoaming ability compared to traditional ordinary tin plating technology. The electrodeposition speed can reach 8μm / min~10μm / min, and the cathode current density is 25A / dm 2 Compared with the traditional bright tin plating deposition rate (about 3μm / min~4μm / min), it is more than 2 times higher, and compared with the traditional bright tin plating cathode current density (3 / dm 2 ~5A / dm 2 ) increased by more than 4 times.
[0114] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A high-strength aluminum-based bright tin wire, characterized in that: From the inside to the outside, it is composed of an aluminum alloy substrate (1), a Cu-Zn alloy bottom layer (2), a Ni-Mo-P intermediate alloy layer (3) and a bright Sn or Sn-Sb alloy layer (4); Calculated by mass percentage of the aluminum alloy matrix (1), the aluminum alloy matrix (1) contains 0.4-0.8% Mg, 0.3-0.6% Si, 0.1-0.3% Mn, 0.01-0.1% Ca, 0.05-0.3% Zn, 0.0001-0.01% B, 0.001-0.1% Ti, Fe≤0.1%, and the balance is Al; Calculated by mass percentage of the Cu-Zn alloy bottom layer (2), the Cu-Zn alloy bottom layer (2) contains 60-80% Cu, and the remainder is Zn; Calculated by mass percentage of the Ni-Mo-P intermediate alloy layer (3), the Ni-Mo-P intermediate alloy layer (3) contains 0.1-0.5% Mo, 2.0-8.0% P, and the balance is Ni; Calculated by mass percentage of the bright Sn-Sb alloy layer (4), the bright Sn-Sb alloy layer (4) contains 1-8% Sb, with the remainder being Sn.
2. The high-strength aluminum-based bright tin wire according to claim 1, characterized in that: The diameter of the aluminum alloy substrate (1) is 2 to 8 mm, and the surface of the aluminum alloy substrate (1) is uniformly provided with arc-shaped grooves along the circumferential direction, the depth of the arc-shaped grooves is 0.01 to 0.1 mm, and the width of the arc-shaped grooves is 0.01 to 0.1 mm; the thickness of the Cu-Zn alloy bottom layer (2) is 0.1 to 1 μm; the thickness of the Ni-Mo-P intermediate alloy layer (3) is 0.5 to 3 μm; and the thickness of the bright Sn or Sn-Sb alloy layer (4) is 1 to 8 μm.
3. The semi-automatic preparation method of the high-strength aluminum-based bright tin wire according to any one of claims 1 to 2, characterized in that: The specific steps are as follows: S1. Preparing an aluminum alloy wire substrate, specifically comprising: S11. Add pure aluminum ingots, aluminum-manganese alloy ingots, aluminum-silicon alloy ingots, aluminum-titanium-boron particles, pure zinc ingots, aluminum-calcium alloy ingots and aluminum-magnesium alloy ingots into a medium frequency melting furnace, heat to a temperature of 680 to 720 ° C to melt to form an aluminum alloy melt, keep the temperature for 1 to 2 hours, then add a refining agent ZnCl2 for refining, slag, cast, and cut to form an aluminum alloy cylinder; S12. The aluminum alloy cylinder is preheated at a temperature of 180 to 240° C., extruded by an extruder to obtain an aluminum alloy wire, and the aluminum alloy wire is annealed at a temperature of 350 to 440° C. for 1 to 3 h to obtain an aluminum matrix rod; S13. The aluminum matrix rod is plastically extruded through the groove of the extrusion wheel to obtain an aluminum alloy wire matrix; S2. The aluminum alloy wire substrate is placed in an aluminum alloy wire electroplating production line for automated surface metallization treatment, which includes, in sequence, aluminum alloy wire substrate pay-off, aluminum alloy wire substrate pretreatment, electroplating of Cu-Zn alloy base layer, chemical plating of Ni-Mo-P intermediate alloy layer, electroplating of bright Sn or Sn-Sb alloy layer, drying and winding; specifically includes: S21. The aluminum alloy wire substrate is degreased by NaOH solution, washed with deionized water, activated with HNO3 solution, and washed with deionized water to obtain a pretreated aluminum alloy wire substrate; S22. The pretreated aluminum alloy wire substrate is placed in a Cu-Zn alloy plating solution for electroplating, and washed with deionized water to obtain a Cu-Zn alloy bottom layer; S23. Plating the aluminum alloy wire substrate with the Cu-Zn alloy bottom layer in a chemical Ni-Mo-P alloy plating solution, and washing with deionized water to obtain a Ni-Mo-P intermediate alloy layer; S24. Plating the aluminum alloy wire substrate with the chemically plated Ni-Mo-P intermediate alloy layer in a bright Sn or Sn-Sb alloy layer electroplating solution, and washing with deionized water to obtain a bright Sn or Sn-Sb alloy layer.
4. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 3, characterized in that: Step S11. The aluminum-manganese alloy ingot is Al-5% Mn, the aluminum-silicon alloy ingot is Al-10% Si, the aluminum-titanium-boron particles are Al-3% Ti-0.5% B, the aluminum-calcium alloy ingot is Al-5% Ca and the aluminum-magnesium alloy ingot is A1-5% Mg; the addition amount of the refining agent ZnCl2 is 1 to 3% of the mass of the aluminum alloy melt.
5. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 3, characterized in that: The aluminum alloy wire substrate pay-off rate in step S2 is 5 to 10 m / min.
6. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 3, characterized in that: Step S21. The concentration of NaOH solution is 50-100 g / L, the degreasing temperature is 60-70°C, and the degreasing time is 40-60 s; the concentration of HNO3 solution is 20-50 wt.%, the activation temperature is 20-40°C, and the activation time is 40-60 s.
7. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 3, characterized in that: Step S22. The Cu-Zn alloy plating solution contains 10-60 g / L copper sulfate, 8-20 g / L zinc oxide, 120-200 g / L potassium pyrophosphate, 10-20 g / L ethylenediaminetetraacetic acid, and 1-2 ml / L OP emulsifier; the electroplating temperature is 20-40 ° C, and the cathode current density is 0.5-2 A / dm 2 , the electroplating time is 0.5 to 2 minutes.
8. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 3, characterized in that: Step S23. The chemical plating Ni-Mo-P alloy solution contains 15-45 g / L nickel sulfate, 5-20 g / L sodium hypophosphite, 5-10 g / L potassium molybdate, and 0.01-0.5 g / L polyethylene glycol 6000. The pH value of the chemical plating Ni-Mo-P alloy solution is 4.0-5.0; the temperature of the chemical plating is 90-100°C, and the time is 5-10 min.
9. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 3, characterized in that: Step S24. The bright Sn layer electroplating solution contains 40-50 g / L Sn 2+ , 100-160g / L methanesulfonic acid, 5-30g / L high-speed tin plating additive; the bright Sn-Sb alloy layer electroplating solution contains 40-50g / L Sn 2+ , 1~5g / LSb 3+ , 100-160g / L methanesulfonic acid, 5-30g / L high-speed tin plating additive; electroplating temperature is 20-50℃, cathode current density is 5-40A / dm 2 , the electroplating time is 20 to 300s.
10. The semi-automatic preparation method of high-strength aluminum-based bright tin wire according to claim 9, characterized in that: The high-speed tin plating additive contains 4-6wt.% methanesulfonic acid, 10-20wt.% surfactant, 1-8wt.% brightener, 0.1-0.5wt.% leveler, 0.1-0.5wt.% stabilizer, 0.1-0.5wt.% anti-scorching agent, and the balance is deionized water.